Conduction lumineuse du vivant - Campeau, Sylvain (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
Abstract Campeau examines the scope and consequences of what seems to be implied by the possibility that objects can produce their own visible radiation, thereby challenging the very notion of photographic reproduction. If light emanates from the body of the object itself, changing its amplitude according to the states of the subject being recorded, then it no longer interferes between the object and the photosensitive surface. Light no longer strikes the object to reveal it. Rather, what occurs between the sensitive plate and the object is instead an exchange and conduction between objects with connections that are still unknown, but can be recorded and seen in the image.